The Pedagogy of Witness. An Anthropological-Kreygmatic Perspective by Zbigniew Marek SJ & Anna Walulik CSFN - the Reflective Challenge for Education - Maria Szymańska (Debrecen University Press, 2020)
Review of the book The pedagogy of witness. An anthropological-kreygmatic perspective, by Zbigniew Marek SJ & Anna Walulik CSFN